A gift to your family. Issue 1 (1st June 2011) - McGregor, D; Porterfield, P; Tolson, M
Abstract : This workshop will describe an initiative within a Canadian health authority (Vancouver Coastal Health, referred to as VCH), in which the Community Engagement Team and the Advance Care Planning (ACP) project leadership partnered to seek this public engagement. To better understand the public's perspectives, and to facilitate greater public acceptance of ACP in our health region, a public forum was held in March 2010. The workshop will outline the forum participants, the program including discussion topics and the outcomes. Themes discussed at the forum included key aspects of public messaging, countering public fear by 'normalising' ACP conversations, and supporting patients and families to have these conversations. It was acknowledged that some members of the public might be mistrustful or worried about the intent and outcomes of ACP and thus the need to emphasize the benefits of ACP, 'a gift to your family'. The forum influenced the emphasis of the ACP project on the importance of communication, the language used for public information, and the ways in which the public are involved in education. At the forum, a number of public participants expressed interest in assisting with public education; subsequently, a group of volunteers has been trained and will present ACP workshops to public groups in our region. The experience of these volunteers will continue to inform our VCH approach to ACP.